Town courts and urban society in late Medieval England, 1250-1500 - Goddard, Richard, 1967-; Phipps, Teresa (The Boydell Press, 2019)
Town courts were the principal institution responsible for the delivery of justice and urban administration within medieval towns. Their records survive in large quantities in archives across England, and they provide an unparalleled insight into the lives and work of thousands of men and women who lived in these towns. The court rolls tell us much about the practice of law at the local level within towns, as well as yielding a broad range of perspectives on the economy, society and administration of towns. This volume is the first collection dedicated to the analysis of town courts and their records. Through a wide range of approaches, it offers new interpretations of the role that these courts played. It also demonstrates the wide range of uses to which court records can be put to in order to more fully understand medieval urban society. The volume draws on the records of a considerable number of towns and their courts across England, including London, York, Norwich, Lincoln, Nottingham, Lynn, Chester, Bromsgrove and Shipston-on-Stour.
Keywords: Great Britain -- History -- Medieval period, 1066-1485.; Law, Medieval -- History -- To 1500.; Court records -- England -- History -- To 1500.; England -- Social conditions -- 1066-1485.; Urbanization -- England -- History -- To 1500.; Grande-Bretagne -- Histoire -- 1066-1485 (Moyen Âge); Angleterre -- Conditions sociales -- 1066-1485.; HISTORY -- Europe -- Great Britain.; Law, Medieval; Court records; Social conditions; Urbanization; Great Britain; England; Justiz; Stadt; To 1500; Black Death.; Chester.; King's Lynn.; Lincoln.; Norwich.; Nottingham.; borough courts.; borough customs.; litigation.; medieval England.; medieval boroughs.; medieval court rolls.; medieval law.; medieval towns.; town courts.; urban history.; urban society.; History